Contributing Factors to the Low Rate of Diverse Female Faculty in Athletic Training Education Programs - Carrie Graham (Adult Education Research Conference, 2018)
This paper presents qualitative data as factors contributing to the disproportionate rate of female faculty across Distinct Racial and Ethnic Identities in athletic training education programs.
Keywords: female faculty of color; microaggressions; mentoring; career advancement